Modifikasi Frekuensi Switching pada LED Driver Menggunakan Oscillator Lorenz Analog untuk Mereduksi Conducted EMI - Mohammad Yanuar Hariyawan; Noptin Harpawi Harpawi (Jurnal Elektro dan Mesin Terapan, 2020)
Light emitting diode (LED) are becoming increasingly popular in a variety of applications, due to low power, high efficiency and low maintenance. To achieve high efficiency, switched mode power supply (SMPS) is applied. SMPS is implemented with pulse width modulation (PWM) which operates at a constant frequency. Constant switching frequency produces significant emissions in a number of frequencies, this emission is called electromagnetic interference (EMI). The EMI generated includes the fundamental operation frequency of the power supply and its harmonics through a conducted and radiated mechanism. As a result, SMPS has the potential to be unable to meet the electromagnetic compatibility (EMC) standard. Modification of switching in SMPS using spread spectrum techniques is a cheap and efficient solution in EMI mitigation. In this research, switching modification is done on LED drivers with chaotic Lorenz signals. The Lorenz chaotic signal is applied to the LED evaluation board and then the EMI performance is seen compared to when the LED driver works with a constant frequency. When applied to the Lorenz chaotic signal there was a decrease in the level of emission of the largest EMI which is equal to 16.5 dBµV